The significance of lipid profile and positive troponin in predicting cardiac event - De Silva, LDR; Kumar, A; Sathian, B (Kathmandu University Medical Journal, 2010)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if !mso]> <![endif]--> <!--[if gte mso 10]> <![endif]--> Background: Diagnosis of Acute cardiac event in the early stage of its onset is important in the treatment process. The development of highly sensitive and specific immunoassays for myocardial proteins such as cardiac Troponin I (cTnI) had made it possible. However Troponin indicates cardiac events only after its onset or after cardiac tissue necrosis. Traditionally such high risk subjects were identified using lipid profiles. The identification of subjects with high risk of developing cardiac event in the future is more significant as it will provide time to prevent such incidents. Objectives: In this study we proposed to study the usefulness of traditional lipid profile levels in screening subjects who had developed chest pain due to cardiac event as indicated by a positive Troponin I test. Materials and methods: In this retrospective study data of the 259 patients presented to the emergency department with symptoms of cardiac ischemia who underwent both Troponin and lipid profiles tests were compared with the lipid profiles of 105 normal healthy subjects (controls). The Trponin was detected qualitatively when a specimen contains Troponin I (cTnI) above the 99th percentile (TnI >0.5 ng/ml). The Total cholesterol (TC), High density lipoproteins cholesterol (HDL), Very low density lipoproteins (VLDL), and Triacyl glycerol levels (TG) were also analysed and low density lipoprotein level (LDL) was calculated using Friedelwald formula. Results: Subjects with chest pain and positive Troponin test (with confirmed cardiac event) were found to have significantly elevated levels of TC, TG , LDL and significantly reduced HDL levels when compared to the subjects who had only chest pain (Negative Troponin) and healthy controls. Conclusion: Traditional lipid profile levels still can be used in screening populations to identify the subjects with high risk of developing cardiac event which is identified by highly sensitive and specific positive Troponin test. Key words: Troponin; Chest pain; Cardiac event; lipid profile DOI: 10.3126/kumj.v7i3.2735 Kathmandu University Medical Journal (2009) Vol.7, No.3 Issue 27, 263-267